ANALISIS AGENDA SETTING PROGRAM BEROBAT GRATIS TANPA BATAS (BERANTAS) KABUPATEN SITUBONDO DENGAN PENDEKATAN MODEL MULTIPLE STREAMS FRAMEWORK - Tauran; Tjitjik Rahaju; Indah Prabawati; Bayu Aditya Ramadhani (Universitas Negeri Surabaya, 2026)
This research is grounded in the crisis regarding the effectiveness of regional health insurance in Situbondo Regency, specifically the failure of the Situbondo Free Healthcare (Sehati) program due to technical constraints regarding cost ceilings and the accumulation of hospital debt, which impeded public accessibility. This situation necessitated a policy transformation toward the Unlimited Free Treatment Program (Berantas). This study aims to analyze the agenda-setting dynamics of the program utilizing John W. Kingdon’s Multiple Streams Framework (MSF). Employing a descriptive qualitative method with a single case study design, data were collected via in-depth interviews with key executive and legislative actors, alongside official documentation studies. The results of the retrospective analysis indicate that the formalization of the Berantas Program into the 2025–2029 Medium-Term Regional Development Plan (RPJMD) was driven by the convergence of three main streams. The problem stream emerged from the fiscal burden of the previous system; the policy stream offered a solution through a more stable hybrid Universal Health Coverage (UHC) scheme; and the politics stream was influenced by the political mandate following the 2024 Regional Head Election. The Regent's strategic role as a policy entrepreneur successfully created a phenomenon of